Quantifying anti-cyclic citrullinated peptide titres: clinical utility and association with tobacco exposure in patients with rheumatoid arthritis. Issue 2 (7th April 2008) - Lee, D M; Phillips, R; Hagan, E M; Chibnik, L B; Costenbader, K H; Schur, P H
Abstract : Objective: To determine the significance of quantitative levels of antibodies to cyclic citrullinated peptides (anti-CCP) in a population of patients with rheumatoid arthritis (RA). Methods: A total of 241 consecutive sera from patients with RA sent from a large rheumatology clinic for laboratory testing were selected for precisely quantifying anti-CCP antibody titres with the anti-CCP2 assay. Patient charts were reviewed for demographic information, smoking history, clinical diagnosis, rheumatoid factor (RF) titre, radiographic information and other laboratory information (erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) level). Correlations with anti-CCP titre and RF titre, disease parameters and smoking history were assessed. Results: We confirm previous findings that anti-CCP seropositivity is associated with a higher incidence of erosions in patients with RA (56% vs 20% CCP+ vs CCP−, κ = 0.297, p<0.001). We also found a moderate correlation between anti-CCP titre and RF titre. However, we failed to find an association between anti-CCP titre and presence of erosions, between anti-CCP titre and CRP or ESR level, or between anti-CCP titre and age or disease duration. Interestingly, we did find significantly higher anti-CCP titres in patients with a history of smoking (452 units/ml vs 229 units/ml, smokers vs non-smokers, respectively; p = 0.02). Conclusions: Although anti-CCP titres were not associated with clinical parameters of disease, they are increased in patients with RA with exposure to tobacco. By contrast, no elevation in RF was noted in patients with a history of smoking. These observations are consistent with a pathogenic contribution of smoking to RA and suggest the immune stimulus for anti-CCP is distinct from that for RF.